2022
DOI: 10.1186/s12913-022-08122-y
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals’ perspectives on the impact of COVID-19 on sexual and gender-based violence (SGBV) and SGBV services in Rohingya refugee communities in Bangladesh

Abstract: Background The COVID-19 pandemic has acutely affected Rohingya refugees living in camps in Cox’s Bazar, Bangladesh. Reported increases in sexual and gender-based violence (SGBV) were attributed in part to pandemic-related public health measures. In addition, the Government of Bangladesh’s restrictions to prevent the spread of COVID-19 have impacted the provision of comprehensive care for survivors of sexual violence. This study sought to understand how the COVID-19 pandemic affected SGBV and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…The predominance of single victims suggests that GBV can occur within various relationship contexts, emphasizing the importance of addressing GBV beyond marital relationships. These ndings align with previous researchers indicating the widespread nature of GBV and its impact on individuals across different demographic backgrounds [29,30].…”
Section: Discussionsupporting
confidence: 92%
“…The predominance of single victims suggests that GBV can occur within various relationship contexts, emphasizing the importance of addressing GBV beyond marital relationships. These ndings align with previous researchers indicating the widespread nature of GBV and its impact on individuals across different demographic backgrounds [29,30].…”
Section: Discussionsupporting
confidence: 92%
“…A 2022 study among Rohingya refugees in Bangladesh showed women and girls were acutely affected by sexual violence and other forms of GBV. The Bangladeshi government, however, deemed sexual and GBV services as nonessential during COVID-19, impeding the ability of providers to continue service provision [67]. An Italian study showed that the COVID-19 pandemic converged with sexism, racism, and xenophobia, resulting in increased harassment and domestic violence against migrant and refugee women; provider and system constraints made access to remote sexual health services particularly difficult [9].…”
Section: Resultsmentioning
confidence: 99%
“…With the added vulnerability resulting from the experiences of the COVID-19 pandemic, there is an urgent need to develop assessment and treatment protocols for traumatized refugees, as untreated trauma can breed further behavioral challenges. For example, there is evidence that refugees experienced financial constraints, heightened discrimination, xenophobia, and sexual and gender-based violence during the COVID-19 pandemic ( Chowdhury et al, 2022 ; Esses & Hamilton, 2021 ; Nisanci et al, 2020 ). All these psychosocial issues can potentially lead to deteriorated mental health and manifestation of PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%